Implementasi Akhlakul Karimah Siswa SMK Negeri 2 Bukittinggi Di Lingkungan Sekolah Tahun Ajaran 2021/2022 - Sintania Wendri; Muhiddinur Kamal; Iswantir M; Charles Charles (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The importance of education makes someone who lives in society experience growth that is oriented towards safety and the highest happiness in life.